Inoculation Pneumonia Caused by Coagulase Negative Staphylococcus - Shi, Meng-meng; Monsel, Antoine; Rouby, Jean-Jacques; Xu, Yan-ping; Zhu, Ying-gang; Qu, Jie-ming (Frontiers in Microbiology, 2019)
Rationale: Although frequently retrieved in tracheal secretions of critically ill patients on mechanical ventilation, the existence of pneumonia caused by coagulase negative staphylococci (CoNS) remains controversial. Objective: To assess whether Staphylococcus haemolyticus(S. haemolyticus) inoculated in mice’s trachea can infect normal lung parenchyma, increasing concentrations of S.haemolyticus, were intratracheally administered in 221 immunocompetent mice. Methods: Each animal received intratracheally phosphate-buffered saline (n=43) or live (n=141) or inactivated (n= 37) S. haemolyticus at increasing load: 1.0 × 106, 1.0 × 107 and 1.0 × 108 colony forming units (CFU). Forty-three animals were sacrificed at H12 and 178 at H36, 64 served for post-mortem lung histology, 157 for pre-mortem bronchoalveolar lavage (BAL) analysis, and 42 for post-mortem quantitative bacteriology of lung tissue. The distribution of virulence-associated genes (icaADBC, aap, atlE, bhp, fbe, empB, mecA) were investigated in the S. haemolyticus strain used in our experiment as well as among other 39 CoNS strains collected from hospitals or nursing houses. Measurements and Main Results: Intratracheal inoculation of 1.0 × 108 CFU live S. haemolyticus caused macroscopic and histological confluent pneumonia with significant increase in BAL white cells count, tumor necrosis factor-α and macrophage inflammatory protein-2. At H12, high concentrations of S.haemolyticus were identified in BAL. At H36, lung injury and BAL inflammation were less severe than at H12 and moderate concentrations of species belonging to the oropharyngeal flora were identified in lung tissue. The inoculation of 1.0 × 106 and 1.0 × 107 CFU live S.haemolyticus caused histologic interstitial pneumonia and moderate BAL inflammation. Similar results were observed after inoculation of inactivated S.haemolyticus. Among the virulence-associated genes screened, mecA was highly expressed by the strain used in our experimental model of pneumonia. Conclusion: In immunocompetent spontaneously breathing mice, inoculation of S.haemolyticus causes concentration-dependent lung infection that spontaneously recovers over time.